Mouse Modeling Dissecting Macrophage–Breast Cancer Communication Uncovered Roles of PYK2 in Macrophage Recruitment and Breast Tumorigenesis. Issue 9 (29th January 2022) - Müller, Anna‐Katharina; Köhler, Ulrike A.; Trzebanski, Sébastien; Vinik, Yaron; Raj, Harsha Mohan; Girault, Jean‐Antoine; Ben‐Chetrit, Nir; Maraver, Antonio; Jung, Steffen; Lev, Sima
Abstract: Macrophage infiltration in mammary tumors is associated with enhanced tumor progression, metastasis, and poor clinical outcome, and considered as target for therapeutic intervention. By using different genetic mouse models, the authors show that ablation of the tyrosine kinase PYK2, either in breast cancer cells, only in the tumor microenvironment, or in both, markedly reduces the number of infiltrating tumor macrophages and concomitantly inhibits tumor angiogenesis and tumor growth. Strikingly, PYK2 ablation only in macrophages is sufficient to induce similar effects. These phenotypic changes are associated with reduced monocyte recruitment and a substantial decrease in tumor‐associated macrophages (TAMs). Mechanistically, the authors show that PYK2 mediates mutual communication between breast cancer cells and macrophages through critical effects on key receptor signaling. Specifically, PYK2 ablation inhibits Notch1 signaling and consequently reduces CCL2 secretion by breast cancer cells, and concurrently reduces the levels of CCR2, CXCR4, IL‐4Rα, and Stat6 activation in macrophages. These bidirectional effects modulate monocyte recruitment, macrophage polarization, and tumor angiogenesis. The expression of PYK2 is correlated with infiltrated macrophages in breast cancer patients, and its effects on macrophage infiltration and pro‐tumorigenic phenotype suggest that PYK2 targeting can be utilized as an effective strategy to modulate TAMs and possibly sensitize breast cancer to immunotherapy. Abstract : This study describes different genetic models to dissect macrophage–breast cancer communication and demonstrates the critical role of the non‐receptor tyrosine kinase PYK2 in this mutual process. PYK2 modulates key signaling pathways mediated by CCL2/CCR2, CXCR4, and IL‐4Rα/pSTAT6, and positively regulates macrophage recruitment and polarization, tumor angiogenesis, and tumor growth.